ANALYSIS OF THE VALIDITY OF NOTARIAL DEEDS IN THE CONTEXT OF NOTARY PRACTICE OUTSIDE THE SCOPE OF THEIR OFFICIAL TERRITORY - I Wayan Mutra; I Nyoman Putu Budiartha; Ni Komang Arini Styawati (NOTARIIL Jurnal Kenotariatan, 2025)
The Republic of Indonesia, as a rule of law state, is committed to ensuring certainty, order, and legal protection for its citizens through regulations governing the notarial office. Notaries, as public officials, have the authority to create authentic deeds, which are important evidence in various legal actions. With a clear legal basis, including Law Number 30 of 2004 and the Civil Code, notaries are required to adhere to applicable regulations and perform their duties with integrity. The creation of authentic deeds must be conducted within the notary's jurisdiction, aimed at protecting public interests. Although this profession has a long history, modern challenges arise when notaries violate regulations, such as operating outside their jurisdiction. Such violations can impact the evidentiary strength of the deeds created. Therefore, it is essential to understand the role of notaries in the context of civil law and to encourage compliance with existing regulations to maintain public trust in legal institutions. This research aims to explore the responsibilities and authorities of notaries as well as the legal implications of violations occurring in practice.